The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.35633/inmateh-62-36
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization and Experimental Research On the Hammer Mill 锤片式粉碎机参数优化与试验研究

Abstract: Low productivity and high electricity consumption are considered problems of the hammer mill, which is widely used in current feed production. In this paper, the mechanical properties of corn grain ground by a hammer mill were analysed, and the key factors affecting the performance of the hammer mill were determined. The single-factor experiment and three-factor, three-level quadratic regression orthogonal experiment were carried out with the spindle speed, corn grain moisture content and number of hammers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…From the analysis of the literature, the topic of the energy demand of the shredding process of grain material is noted worldwide, and hammer shredders are the most common design in the implementation of the industrial grain milling process. This is also demonstrated by the studies presented by Wang [9,10], who carries out an analysis of the mechanical properties of maize grain and identifies the key factors affecting the operation of a hammer shredder. Also the analysis of a new shredder screens design in order to improve the process efficiency has been conducted.…”
Section: Introductionmentioning
confidence: 82%
“…From the analysis of the literature, the topic of the energy demand of the shredding process of grain material is noted worldwide, and hammer shredders are the most common design in the implementation of the industrial grain milling process. This is also demonstrated by the studies presented by Wang [9,10], who carries out an analysis of the mechanical properties of maize grain and identifies the key factors affecting the operation of a hammer shredder. Also the analysis of a new shredder screens design in order to improve the process efficiency has been conducted.…”
Section: Introductionmentioning
confidence: 82%
“…(2) Response surface analysis of missed pulling rate and pull-off rate To express vividly the significance of the influence of each test factor on the working performance of the machine, a 3D response surface model (Shi et al, 2023) was established, and the consistency between the influencing trend of each factor on evaluation indexes and the analysis result of variance was assessed (Jiang et al, 2024), as shown in Figure 7.…”
Section: Levelmentioning
confidence: 99%
“…The force analysis diagram is shown in Figure 3. According to impulse theorem and momentum theorem (Wang et al, 2020), the following formulas can be obtained:…”
Section: Force Analysis Of Corn Grainmentioning
confidence: 99%
“…The grinding of cereal feed can increase its surface area, which is beneficial for improving the digestibility and palatability of feed (Dey et al, 2013;Ghodki & Goswami, 2018). Hammer mills have the widest application due to their advantages of simple structure, good versatility and convenient maintenance (Wang et al, 2020;Bochat et al, 2015;Nakamura et al, 2015). However, hammer mills exhibit low productivity and high energy consumption in production (Polari & Wang, 2019;Tian et al, 2018;Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%